Prognostic stratification based on the levels of tumor-infiltrating myeloid-derived suppressor cells and PD-1/PD-L1 axis in locally advanced rectal cancer - Lim, Yu Jin; Koh, Jaemoon; Choi, Minji; Kim, Sehui; Chie, Eui Kyu (Frontiers in Oncology, 2022)
Background: Although rectal cancer remains somewhat sanctuary to the contemporary immunotherapy, there is increasing knowledge on clinical implications of anti-tumor immunity. This study evaluated the prognostic relevance of two immune-inhibitory functions, myeloid-derived suppressor cells (MDSCs) and programmed cell death-1 (PD-1)/programmed death-ligand 1(PD-L1) axis. Methods: Study cohort is comprised of 165 patients with locally advanced rectal cancer who underwent neoadjuvant chemoradiotherapy followed by definitive resection. Using postsurgical tissue microarrays, the number of MDSCs, PD-1+/CD8+ tumor-infiltrating lymphocyte (TIL) ratio, and PD-L1 expression scores in stromal immune cells and tumor cells were assessed. Results: Positive correlation was observed between the PD-1+/CD8+ TIL ratio and number of MDSCs (P < 0.001). The greater the immune infiltrates, the higher the PD-L1 immune cell score (P < 0.001). MDSCHigh, PD-1+/CD8+ TILHigh, PD-L1 immune cell scoreLow, and PD-L1 tumor H-scoreHigh were associated with worse disease-free survival (DFS) (P < 0.001, P = 0.042, 0.047, and P < 0.001, respectively). To integrate the adverse effects of MDSCHigh, PD-1+/CD8+ TILHigh, and either PD-L1 immune cell scoreLow (set I) or tumor H-scoreHigh (set II), prognostic risks were stratified according to the number of factors: 0, 1, and 2‒3 (P < 0.001 for I and II). On multivariate analyses, patients with multiple risk factors for set I and II had worse prognosis (P < 0.001; 2‒3 vs. 0 for models I and II), and the two prognostic models had acceptable predictability. Conclusion: In this study, integration of the prognostic impact of MDSCs and PD-1/PD-L1 stratified the long-term risks of patients with locally advanced rectal cancer. Thus, further exploration could be focused to the identified subset of patients carrying worse prognosis, where potential benefits could be derived by targeting the two components contributing to the immunosuppressive microenvironment.